Cultura organizacional como fator de influência no ciclo de gestão do conhecimento - Fukunaga, Fernando (2015)
The perception of knowledge as an economic good and the strategic importance of organizational culture has been suggested and studied by several authors. This research has as main objective to analyze the influence of the attributes of organizational culture, from the theoretical model of Quinn and Cameron (2006), to the success of knowledge management cycle based on the model suggested by Lawson (2002). As strategy and methodological principles was selected the single case study method. The methodological procedure had a quantitative approach and qualitative approach defining it as a method of triangulation. Research was conducted on a large national company in the engineering and infrastructure segment. The quantitative approach had a final sample of 14 leaders as participants valid online survey respondents, qualitative approach with participants of the three levels of the organization studied: strategic, tactical and tactical-operational. The main results showed a strong relationship between organizational culture and knowledge management. Several evidence was found and it is estimated that these can be generalized and help other organizations to seek successful implementation or support of knowledge management